A research agenda for place branding - Medway, Dominic; Warnaby, Gary; Byrom, John (Elgar research agendas., 2021)
"Elgar Research Agendas outline the future of research in a given area. Leading scholars are given the space to explore their subject in provocative ways, and map out the potential directions of travel. They are relevant but also visionary. This cutting-edge Research Agenda for Place Branding explores ideas and debates that inform a refreshing take on the future of place branding and marketing. It argues that we are at a juncture where the logical and sensible step is to push the 'reset button' on such activity and fully reconsider its purpose and goals. Chapters span a range of important themes in contemporary place branding and are organised into sections covering place branding governance, contexts, experience and creativity. Drawing on contributions from key international scholars across a variety of academic disciplines, the book showcases an interplay of oppositional perspectives - ranging from those who see place branding as a potential means of improving the economic vitality of places, to others who consider much existing place branding activity exclusionary to certain sectors of society. Providing a wealth of creative and innovative suggestions on how place branding can be done, thought about and researched differently in the future, this Research Agenda will be a key resource for research-oriented academics and students in marketing, geography, planning and tourism"-- Provided by publisher.